Illustration- Colmar - France (5520389918) - Guy MOLL from Faro... (Wikimedia Commons, 2011)
Notice iconographique issue de Wikimedia Commons. Titre: Illustration- Colmar - France (5520389918). pour une fois, quelquechose de différent: style illustration (encre et aquarelle) / for once, something different: illustration style (ink and watercolor)
Droits : Licence Creative Commons Attribution 2.0 via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie